P-39 Mountbatten memories. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Topping, Emma; Hartley, Nigel
Abstract : Background: A few plastic boxes containing old photos and typed notes tucked away in an office were all that existed to share the story of our hospice's 35 years. Thanks to a successful National Lottery bid, we set about bringing our story to life, through the recording of people's memories to form an oral history project called 'Mountbatten Memories.' Aims: To share our history with a wider population, therefore inspiring others to be involved in our future. To consolidate our place in the Island's health and social care environment, and in the hearts and minds of our community. To provide opportunities to reconnect people through their past involvement and to build new and diverse skills in volunteers, for example, audio editing and interviewing. Methods: We based a series of reminiscence events in our hospice shops, ensuring our wider community's involvement in, and awareness of, the project. Additional interviews were gathered from former staff and volunteers. Around 50 interviews have been gathered from a diverse range of people involved in the hospice's development from the first clinical staff and volunteers, to those who supported with initial fundraising events and families who received care over the past 35 years. The audio interviews have been shared on our website, alongside archive BBC footage. A multi-media exhibition is being shown at events throughout the year. Results: During the first staging of the exhibition, former staff and volunteers were reconnected through their collective memories and people were educated about our hospice's development. It has provided further opportunities to communicate about our work and future plans, and equipped volunteers with new skills. Conclusions: We now have a repository where many precious memories form a lasting legacy, capturing the story of our hospice for a much wider audience and for future generations.